Analisis Sensitivitas pada Model Matematika Transmisi Pengguna Narkoba dengan Faktor Edukasi - Anissa Dwi Wijayanti; Lailany Yahya; Agusyarif Rezka Nuha; Resmawan Resmawan (Jurnal Matematika Integratif, 2020)
Drugs have a bad effect on the users which is mental disorders and health problems even causing death. Cases of drug users spread can be formulated with a mathematical approach through the concept of mathematical modeling. This article discusses the mathematical model of SURS type drug users spread. Model development by adding educational factors to each population class. Furthermore, the basic reproduction number () is constructed to model the threshold value of the spread of drug addicts. The basic reproduction number is determined by using a Next Generation Matrix approach. The next step is to do a sensitivity analysis to determine the parameters that most influence the spread of drug addicts. Based on the analysis results, the parameters β and indicate the most dominant sensitivity index to the basic reproduction numbers. At the end of this article, a simulation is carried out to show the effect of changing parameters on the population of drug addicts.